Analisis Perbandingan Pemahaman Mahasiswa Universitas Negeri Medan dari Berbagai Jurusan Terhadap Penegakan Hukum Tindak Pidana Korupsi - Dinda Dwi Aprillia; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Kevin Jeremi Doniartha Saragih; Mey Wulandari Simanullang; Adelsiza Zenoni Harianja; Amelia Kartika (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Law enforcement against corruption is a vital aspect of maintaining the integrity of the Indonesian nation, considering that corruption has become a widespread and systemic phenomenon across various sectors. In this context, students, as agents of change, play an important role in overseeing legal enforcement issues. Unfortunately, understanding of anti-corruption laws remains uneven among students from different academic disciplines. This study uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation involving 10 respondents from various departments at Universitas Negeri Medan. The purpose of this research is to analyze the level of understanding, differences in perspective, and the concern of students across disciplines toward the enforcement of anti-corruption laws in Indonesia. The findings reveal variations in understanding based on academic background, yet most students acknowledge the importance of integrating anti-corruption education across all majors as a preventive step to foster legal awareness and integrity from an early stage.